Foreign method of calculating the cost of production - Djumanov, S.A. (Академик Е.А.Бөкетов атындағы Қарағанды университетінің баспасы, 2024)
The article considers the main types of modern methods of analysis and accounting of production costs, product (works, services) costs. Here, the concepts and traditional approaches of product costing popular in domestic and foreign countries and common methods in foreign practice are described.
Keywords: calculation; modern methods of costing; traditional methods of costing; profit; management decisions; national standards of accounting; international standards of financial reporting